Foreword - Demirji, Muayad Sa’id
ersch. 1987; Mu’ayyad Sa’?d Damir??; Activities of the Iraq Museum. Directorate General of Antiquities and Museums of Central Region — Western Region — Northern Region. Foreign Expeditions. Directorate of the Antiquities of the Governorate of Arbil. Mosul